Predictive Analysis of Consumer Behaviour and Brand Preference Using Data Science: A Case Study of Nigerians In The United Kingdom - Okemili, Linus Emeka; Danquah , Joseph (International Journal of Scientific Research and Management (IJSRM), 2025)
This study looks into the brand preferences and purchasing habits of Nigerian immigrants residing in the UK's West Midlands. The study combines convenience sampling with snowball sampling in a quantitative manner to collect data from 76 participants. It examines brand affinities between Nigerian and Western companies as well as generational variations in first- and second-generation Nigerian immigrants' brand perceptions. An online survey conducted through Google Form served as the primary data collection tool. Apart from recommendations from existing members, the participants were recruited through multiple online platforms: Facebook, LinkedIn, and WhatsApp. According to the report, immigrants from Nigeria strongly prioritize affordability as well as quality, giving price (68.4%) and quality (71.1%) considerable weight when making decisions. The distribution of preferences across Western and Nigerian companies shows how important cultural familiarity is when choosing a brand. The study also uncovers age variations, with younger immigrants exhibiting a preference for Westernized goods, suggesting a shift caused by cultural adaptation. The results provide valuable insights for marketers and firms aiming to connect with this demographic; however, the extent to which the findings may be applied is restricted by sample size and regional focus. This study contributes to our understanding of the intricate consumer behaviours of Nigerian immigrants in the UK by offering helpful recommendations for prudent marketing strategies.